The Effect of Peer Scaffolding on Iranian EFL Learners’ Listening Comprehension - Karim Shabani; Sekineh Malekdar (Journal of Modern Research in English Language Studies)
This study investigated the extent to which peer scaffolding could contribute to the listening comprehension on Iranian EFL learners with elementary level of language proficiency. To fulfill this objective, 33 institute students were selected through Key English Test (KET) and assigned to two groups in experimental (scaffolding group) and control (non-scaffolding group). After the participants’ initial level of listening comprehension was measured by a pre-test, the interactive strategies of scaffolding were given to the experimental group in 10 sessions and the two groups’ achievement was measured by a post-test and a delayed post-test. The results of T-test indicated that collaborative scaffolding strategies were effective in enhancing EFL learners’ listening comprehension and the experimental group outperformed the control group. Also, the result of the qualitative data analyzes showed the use of peer scaffolding strategies in the experimental group and employment of L1 and background knowledge in the task performance. The frequency analyses of the detected strategies revealed a peer –peer scaffolding framework. On implication side, this study could prescribe different individual learning plans for learners with different learning needs.